First-principles study of structural and electronic properties of ZnSe with wurtzite structure - Jafarova, V.N; Musaev, M.A (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Using Density Functional Theory (DFT) and Local Spin Density Approximation (LSDA) the structural and electronic properties of pure ZnSe wurtzite compound were theoretically investigated. The Hubbard U semiempirical correction has also been used to improve the underestimated DFT calculated band gap. From the DFT+LSDA+U method obtained that the wide of band gap is 2.7 eV and this result is closer to the available experimental results. Current studies reveal that the maximum of valence band and the minimum of conduction band located at the Γ (0, 0, 0) symmetry point on the Brillouin zone. Accurate investigation of the electronic structure of studied material is helpful for the technical applications.